On the use of repeat leveling for the determination of vertical land motion: artifacts, aliasing and extrapolation errors - Lyon, Todd; Filmer, Michael; Featherstone, Will (Wiley-Blackwell Publishing, 2018)
Leveling remains the most precise technique for measuring changes in heights. However, for the purposes of determining vertical land motion (VLM), a time series of repeat leveling measurements is susceptible to artifacts and aliasing that may arise due to systematic errors, seasonal surface fluctuations, motions occurring during a survey, and any inconsistencies in the observation conditions among epochs. Using measurements from 10 repeat leveling surveys conducted twice yearly along a profile spanning ~40 km across the Perth Basin, Western Australia, we describe the observation, processing, and analysis methods required to mitigate these potential error sources. We also demonstrate how these issues may lead to misinterpretation of the VLM derived from repeat leveling and may contribute to discrepancies between geologically inferred rates of ground motion or those derived from other geodetic measurement techniques. Finally, we employ historical (~40‐year‐old) leveling data in order to highlight the errors that can arise when attempting to extrapolate VLM derived from a geodetic time series, particularly in cases where the long‐term motion may be nonlinear.